Fatigue-Induced Scapular Dyskinesis in Healthy Overhead Athletes - Zago, Matteo; Kawczyński, Adam; Klich, Sebastian; Pietraszewski, Bogdan; Galli, Manuela; Lovecchio, Nicola (Frontiers in Bioengineering and Biotechnology, 2020)
Word count: 2387 2 ABSTRACT Alterations of scapular kinematics affect the whole kinematic chain, potentially leading to the impingement syndrome. This is crucial in overhead sports, where athletes perform frequent and quick upper limb actions. In this paper, we aimed to assess the extent to which fatigue alters scapulo-thoracic and scapulo-humeral ranges of motion (RoM), as well as scapulo-humeral movement onset during different upper limb actions. Twenty-four young healthy males aged 22±2 years (height: 1.82±0.06 m, body mass: 78.0±7.8 kg) performed three movements (upper limb elevation, scapular-plane abduction and intra-extra rotation) before and after an isokinetic fatigue protocol (upper limb intra/extra rotation, 32 repetitions at 120 degrees/s). Pre vs. post fatigue RoM of humeral elevation and rotation, scapular retraction/protraction, rotation and tilt were computed. Humerus-scapula movement delay was also determined. Humerus elevation range reduced during intra/extra humerus rotation in fatigued conditions (p=0.006). Scapular tilt RoM increased after the fatigue protocol (p=0.063, large effect). Humerusscapular movement onset delay reduced in fatigued conditions of about 80 ms (p<0.001, large effect). In sum, fatigued intra/extra upper limb rotators altered the scapulohumeral rhythm and joints RoM in movements outside the scapular plane. Rather, movements close to the scapular plane were less prone to fatigue-induced alterations.